2001
DOI: 10.1029/2001jd000465
|View full text |Cite
|
Sign up to set email alerts
|

Mean ages of stratospheric air derived from in situ observations of CO2, CH4, and N2O

Abstract: Abstract. Accurate mean ages for stratospheric air have been derived from a spatially and temporally comprehensive set of in situ observations of CO2, CH4, and N20 obtained from 1992 to 1998 from the NASA ER-2 aircraft and balloon flights. Errors associated with the tropospheric CO2 seasonal cycle and interannual variations in the CO2 growth rate are ( 0.5 year throughout the stratosphere and ( 0.3 year for air older than 2 years (N20 < 275 ppbv), indicating that the age spectra are broad enough to attenuate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
315
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(344 citation statements)
references
References 52 publications
(41 reference statements)
17
315
1
Order By: Relevance
“…Upward transport of air masses from the TTL into the tropical stratosphere is controlled by the large-scale dynamics of the Brewer-Dobson circulation implying comparatively slow ascent that leaves time for horizontal mixing and for processing of organic source gases to inorganic product gases. Ascent velocities in the tropical lower stratosphere are estimated to a few tenths of a mm/s implying that the mean time since air masses around 20 km (∼475 K) entered the stratosphere is several months (Andrews et al, 2001;Schoeberl et al, 2008). We concede that our observations in the tropical tropopause layer might be affected by local variability of air masses.…”
Section: Discussionmentioning
confidence: 88%
“…Upward transport of air masses from the TTL into the tropical stratosphere is controlled by the large-scale dynamics of the Brewer-Dobson circulation implying comparatively slow ascent that leaves time for horizontal mixing and for processing of organic source gases to inorganic product gases. Ascent velocities in the tropical lower stratosphere are estimated to a few tenths of a mm/s implying that the mean time since air masses around 20 km (∼475 K) entered the stratosphere is several months (Andrews et al, 2001;Schoeberl et al, 2008). We concede that our observations in the tropical tropopause layer might be affected by local variability of air masses.…”
Section: Discussionmentioning
confidence: 88%
“…For completeness, we compare the CLaMS simulated mean age of air with this data set. Figure A1 compares latitudinal profiles of CLaMS simulated mean age of air at 20 km, AoA based on MIPAS observations of SF 6 [Haenel et al, 2014] and on airborne in situ observations of SF 6 and CO 2 (same data as shown in Waugh and Hall [2002], based on various measurements, [Boering et al, 1996;Andrews et al, 2001;Elkins et al, 1996;Ray et al, 1999;Harnisch et al, 1996]). The shadings show the range of monthly mean values for CLaMS and MIPAS, while the error bars show the range between minimum and maximum in situ observations in each latitude bin.…”
Section: Appendix A: Comparison Of Simulated Mean Age To Observationsmentioning
confidence: 99%
“…Stratospheric CO 2 profiles are generated from the age of air relationship derived by Andrews et al [53]. The H 2 O a priori profiles come from the NCEP/NCAR analysis for that day, interpolated to local noon, with stratospheric VMRs based on MkIV balloon profiles.…”
Section: (Iii) a Priori Profilesmentioning
confidence: 99%